Effect of nursing risk management on safety goals of cancer patients during the transition period after discharge from ICU (护理风险管理对ICU转出肿瘤患者过渡期安全目标的影响) - GAO Fei (高菲); ZHANG Jianhua (张建华) (Association of Integrative Nursing, 2021)
Objective To investigate the effect of nursing risk management on safety goals of cancer patients during the transition period after discharge from ICU. Methods A risk management team for cancer patients after discharge from ICU was set up. The high risk factors during the transition period after discharge from ICU were evaluated according to the practice guidance of patient safety goals. The high-risk screening system, detailed implementing rules, cost-effectiveness evaluation and quality control process were carried out. The nurses' perception of risk and patients' satisfaction with nursing risk management were evaluated. Results There was a significant increase in the ability of risk identification and self-evaluation after implementation of risk management (P<0. 01). The satisfaction degree of patients after implementation of risk management was higher than that before implementation of risk management (P<0. 01). Conclusion Implementation of nursing risk management can enhance the nurses' ability of risk identification and improve the satisfaction of patients during the transition period after discharge from ICU. (目的 探讨护理风险管理对肿瘤患者ICU转出后过渡期安全目标的影响。方法 成立ICU转出患者护理风险管理小组, 参照《患者安全目标实践指南》, 评估肿瘤患者ICU转出后过渡期高危因素, 构建护理风险排查机制, 制定护理风险管理实施细则, 基于患者安全目标建立过渡期护理风险管理成效评估及质控流程。对比实施护理风险管理前后护士风险认知水平和患者对护理风险管理实施的满意度。结果 实施护理风险管理后护士识别风险能力较实施前提高, 个人自评优于实施前, 差异有统计学意义(P<0. 01)。实施护理风险管理后患者对护理安全管理满意度高于实施前, 差异有统计学意义(P<0. 01)。结论 通过对ICU转出肿瘤患者过渡期实施护理风险管理, 能够提高护士识别风险能力水平和患者满意度。)